2019
DOI: 10.1159/000495765
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide Stress Test as a Predicting Biomarker for Delayed Graft Function in Kidney Transplantation

Abstract: Background: Delayed graft function (DGF) could worsen early and long-term outcomes of kidney transplantation (KT). DGF is caused by several pre-transplantation and perioperative factors in both donors and recipients. At present, there are no biomarkers or tests during the immediate post-KT period that can accurately predict the development of DGF. Materials and methods: This prospective study was conducted in deceased donor KT (DDKT) at King Chulalongkorn Memorial Hospital, Thailand. All recipients underwent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Furosemide is the most commonly used loop diuretic. It has been used to predicting progression of AKI with the so-called furosemide stress test (FST) in non-transplant patients (145,146). Loop diuretics can also provide prognostic value in regard to renal allograft function in the immediate post-transplant period.…”
Section: Loop Diureticsmentioning
confidence: 99%
“…Furosemide is the most commonly used loop diuretic. It has been used to predicting progression of AKI with the so-called furosemide stress test (FST) in non-transplant patients (145,146). Loop diuretics can also provide prognostic value in regard to renal allograft function in the immediate post-transplant period.…”
Section: Loop Diureticsmentioning
confidence: 99%
“…Ideally, kidneys will be neither wasted nor used in poor condition. Of course, it is difficult to achieve this, and additional in-depth evaluation systems, such as molecular markers, irrigation fluid culture, susceptibility-weighted imaging and other information, need to be further investigated to improve quality of organ transplantation [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…This test performed better than many of the urinary biomarkers used to predict AKI. Subsequent studies of FST in AKI have demonstrated that the FST performance is robust and performs consistently for the assessment of AKI progression and recovery [45][46][47][48].However, none these studies measured the excreted mass of furosemide.…”
Section: Discussionmentioning
confidence: 99%